ANALISIS EFISIENSI PEMASARAN KEDELAI DI KABUPATEN WONOGIRI - SUTARNO SUTARNO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2014)
The objectives of the research wre to study theresearch were to study the farmers share and benefits on each marketingÂ institution, marketing margin of each marketing institusion , and to evaluate the factorsÂ affecting soybean marketing. The study showed that the marketing margin soybean was affected by quality of marketing soybean , number of marketing intitusion involved, distance of producer and trader and transaction system. The implicasion of this study was supposed to be an input for local government in developing the decision to increase farmers poverty and farmers ability based on agribusnees concept and local condition.